The Assessment of Some Serum Biomarkers of Fibromyalgia Syndrome in Pre and Postmenopausal Women in Relation to Obesity - Saleh, Eman S. (Iraqi Journal of Pharmaceutical Sciences, 2019)
The objective of this study is to evaluate the level of parathyroid hormone, Co enzyme Q and total antioxidant status in serum’s women with fibromyalgia syndrome firstly, then to demonstrate if these biochemical markers affected by age and obesity. This study was performed at Rheumatology and Rehabilitation Consultation Unit in Baghdad Teaching Hospital. Venous blood sample were drawn from (59) female with FMS and (30) control (without FMS). The serum was obtained after on standing in order to coagulate then centrifuged. The mean age± SD of FMS group was (42.22±15.34) years and for control was (40.7±18.22) years. Those participants were subdivided into four different groups according to menopausal status and body mass index to estimate three biochemical markers in their serum. The assessment of serum both PTH and Co enzyme Q were done by enzyme linked immune sorbent assay (ELISA) while total antioxidant status (TAS) determination was done colorimetric ally. Statistical analysis was calculated by SPSS program version 24. Independent samples T-test for different group of patients Pearson correlation between serum’s biomarkers within different groups; P values < 0.05 means significant. The results record that serum’s PTH showed increasing significantly at same time of decreasing Co Q (P value<0.05) but TAS measuring register not significant decreased (P value> 0.05) in FMS comparing with control group. About the age; PTH serum level appear insignificant increased but Co Q & TAS were decreased (P value >0.05& P value< 0.05) respectively in post menopause comparing with pre menopause. For estimating serum’s biomarkers related with body mass index (BMI) as a sign of obesity. Serum PTH level record significant raise in obese group P value<0.003, insignificant variation in obese and non- obese groups (P value>0.05) in the same time TAS record a significant decrease in obese group P value= 0.00.In pre menopause (FMS and control): Serum TAS level correlate negatively and significantly with PTH (P value= 0.034). For age>55; PTH in both FMS& control show critical significant correlation P value=0.05. In pre and post menopause FMS show significant independent t-test belong to TAS (P value= 0.004). In obese group PTH correlate Co Q of 25<BMI>30 significantly P value=0.027 and P value=0.029. T test show significant in PTH and TAS between obese and non-obese.In conclusion the obesity and menopause play an imperative role in the etiology of FMS relative with serum’s biomarkers (PTH, Co Q and TAS).